Association Between Endometriosis and Lower Urinary Tract Symptoms [34F]. (May 2020) - Gabriel, Iwona; Vitonis, Allison; Missmer, Stacey; Terry, Kathryn; DiVasta, Amy; Minassian, Vatche
Abstract : INTRODUCTION: Lower urinary tract symptoms (LUTS) as frequency, urgency, nocturia, and dysuria significantly affect women of all ages. We hypothesize LUTS are more commonly experienced by women with endometriosis than without. METHODS: We conducted a cross-sectional study of 1161 women who participated in The Women's Health Study: from Adolescence to Adulthood. At baseline, participants completed questionnaire that included questions on the following LUTS in the past three months: loss of urine when coughing, sneezing or laughing; difficulty passing urine; blood in the urine; still feeling full after urination; and having to urinate again within minutes of urinating, dysuria (pain >5 in 1-10 scale). Women who did not complete LUTS questions or who reported frequent bladder infections were excluded. We used logistic regression modelling adjusted for race, current age, BMI, parity to estimate odds ratios (OR) and 95% confidence intervals (CI) of the associations between endometriosis and LUTS. The study was approved by IRB. RESULTS: Participants were predominantly white non-Hispanic (89% of cases, 72% -controls) and nulliparous (95% of cases, 91% -controls), with age range 7-55. Participants with endometriosis more frequently reported still feeling full after urination (77% vs. 23%, OR 5.14, CI 3.23-8.18), having to urinate again within minutes (61% vs. 39%, OR 2.45, CI 1.81-3.32), difficulty passing urine (76% vs. 24%, OR 3.41, CI 1.71-6.81), and dysuria (66% vs. 35%, OR 2.58, CI 1.57-4.26). LUTS were not associated with duration of endometriosis symptoms nor rASRM stage. CONCLUSION: Women with endometriosis report LUTS significantly more often than those without. Addressing LUTS may improve the wellbeing of women with endometriosis.